Options for Improved Treatment of Saline Wastewater From Fish and Shellfish Processing - Anh, Hoang Thi Hong; Shahsavari, Esmaeil; Bott, Nathan J.; Ball, Andrew S. (Frontiers in Environmental Science, 2021)
The rapid growth of the aquaculture industry over recent decades, resulting in annual production reaching 71 million tonnes in 2016 has resulted in a significant increase in saline wastewater following the use of seawater in both fish and shellfish production and processing. This wastewater contains high concentrations of nutrients, organic compounds, and total nitrogen, requiring significant treatment prior to discharge to meet environmental regulations, which are becoming more stringent. The infrastructure and running costs associated with physico-chemical treatment approaches are generally higher than the implementation of biological approaches the latter represents both an economic and sustainable technology. However, salinity represents a significant inhibitor to microbial activity affecting the efficacy of the biological treatment of the wastewater. The option to enhance saline wastewater biological treatment approaches such as bioaugmentation represents a potential approach to the aquaculture industry to meet future discharge regulations This review will (1) identify the major biodegradable components in saline fish wastewater that may result in deleterious effects upon discharge, (2) discuss the current methods used in aquaculture for the treatment of wastewater processes, and (3) identify opportunities for improved processes to be utilised and identify gaps in knowledge require further research.